ASPEK HUKUM GOLONGAN PUTIH DALAM PEMILIHAN UMUM - Ni Putu Noni Suharyanti (Jurnal AKSES, 2020)
In the implementation of elections in Indonesia, both legislative elections, presidential elections or regional head elections, there is always a phenomenon of white group voters or often known as "golput". The existence of these abstentions turned out to be pro-contra in society because they were considered to have implications for the development of democracy in Indonesia. People also often wonder whether the attitude of abstentions can be subject to sanctions or punishment. Based on this background, problems can be formulated which are the implications of abstentions in the development of democracy in Indonesia and how the legal aspects of abstentions in general elections. This study uses normative legal research. In the framework of developing democracy in Indonesia, the existence of abstentions certainly has implications especially for the electoral process which is part of the implementation of democracy. However, the attitude of abstentions in general elections based on the Act cannot be punished because the attitude of abstentions is a political right, so that those who have the opportunity to be punished according to the Act are those who influence or invite others not to exercise their right to vote (abstentions).